CHANGES IN THE URBAN TOPONYMIC SPACE OF KHARKIV IN THE PROCESS OF DECOMMUNISATION - Мірошниченко, Вадим (SWorldJournal, 2025)
The article analyzes the change in the urban toponymic space of Kharkiv in the process of decommunization as a reflection of the specific multilayered local historical memory of Kharkiv residents. A prominent place is given to the formation of the local h